The Modified Quadrature Method for solving Volterra Linear Integral Equations (Baghdad Science Journal, 2014)
In this paper the modified trapezoidal rule is presented for solving Volterra linear Integral Equations (V.I.E) of the second kind and we noticed that this procedure is effective in solving the equations. Two examples are given with their comparison tables to answer the validity of the procedure.